The Capital Structure through the Trade-Off Theory: Evidence from Tunisian Firm - Ghazouani, Tarek (International Journal of Economics and Financial Issues, 2013)
The objective of this paper is to study the capital structure of firms and the explanation of their behavior in the context of trade-off theory. It analyzes the determinants of capital structure of Tunisian firms through the existence or not of a dynamic model of adjustment to target leverage ratio. This validation leads to test two complementary successive models, the first is a static, while the second is a dynamic model that incorporates transaction costs variable to see how we can talk about a speed adjustment allowing firms to get closer to the target ratio. The results of the first model show that the profitability and asset structure are the main explanatory variables of the level of leverage of Tunisian firms. While for the dynamic model, the most remarkable result is manifested at the level of the adjustment costs that are relatively high which engendered a slow adjustment towards the optimal ratio. Keywords: Capital structure; Trade-Off Theory; Static model; Dynamic model; Panel data. JEL Classifications: C33; G31; L25